Tuberculosis of the Malar and Zygomatic bone: A case report - Al-Hazmi, Waleed Abdulaziz (International Journal of Health Sciences, 2011)
A young female presented with painful swelling of right lower neck followed by swelling in the left side of the face associated with dental infection. There was no history of systemic illness. Family history for pulmonary tuberculosis was negative. The hematological, serological and biochemical investigations were normal, however, tuberculin test was strongly positive.Â CT scan of the face and neck showed a ring-enhancing swelling over the left zygomatic bone with underlying bone erosion and right lower neck lymphadenopathy. The affected areas were excised and histopathology confirmed chronic granulomatous inflammation consistent with tuberculosis of the zygomatic bone. Patient responded to anti-tuberculosis treatment and showed significant improvement upon 9 months follow up.Â Head and neck tuberculosis can confuse with cancer.Â This case is presented to make awareness of this rare condition and to familiarize the clinicians. So far only few cases of primary tuberculosis of zygomatic bone have been reported in the literature. Key words: Tuberculosis, malar, zygomatic bone, dental infection.